Creative tourism experience: exploring the influence of novelty-seeking, perceived coolness and servicescape on behavioral intention - Sri Astuti Pratminingsih; Fansuri Munawar; Christina Lipuringtyas Rudatin (Cogent Business & Management)
Creative tourism is currently a growing market, presenting both opportunities and challenges for destination managers in providing unique and engaging tourist experiences. Although the concept has been widely explored, investigations on specific factors shaping creative tourism experience (CTE) and the influence on behavioral intention remain limited. Therefore, this research was aimed to address the existing gaps by examining the influence of novelty-seeking, perceived coolness and servicescape on hedonic well-being and behavioral intention of tourists in creative tourism context. Data were collected through questionnaires from 312 tourists visiting one of the four categories, including art, technology, knowledge and sports-based creative tourism, in Bali, Yogyakarta and Bandung, Indonesia. Additionally, structural equation modeling using partial least squares was applied for quantitative analysis. The results showed that novelty-seeking, perceived coolness and servicescape significantly enhanced CTE, positively influencing hedonic well-being and behavioral intention, while gender moderated the relationship between novelty-seeking and CTE. These contributed to a deeper understanding of the role of CTE in influencing well-being and intention, offering valuable theoretical insights into creative tourism. Strategies were practically suggested for destination managers to enrich the experiences of tourists, fostering repeated visits and promoting positive word-of-mouth for creative tourism destination.